An outline of the geometric proportion systems in architecture - Januszewski, Wojciech (Zarys problematyki geometrycznych systemów proporcji w architekturze, 2023)
Proportional systems are arithmetic or geometric methods of organizing architectural form that determine the mutual proportional relationships of the parts and the whole of an architectural work. The theory of these systems, developed over the centuries, constitutes an essential component of architectural theory, deserving of rediscovery and reinterpretation in our era. The purpose of this study is to present a synthetic overview of the issues related to geometric proportional systems in architecture. The article adopts an interdisciplinary approach, integrating the history and theory of architecture with elements of practical geometry. The research method encompasses a literature analysis and an examination of selected geometric methods applied to specific design problems. The article offers an original perspective on geometric proportional systems, interpreting them as a coherent theory based on interconnected elements, such as similarity of figures, regulating lines, regular shapes, and dynamic symmetry. The study portrays proportional systems as a set of flexible design methods rooted in elementary geometric principles, empowering architects to better control the visual relationships of their designed objects of architecture. Simultaneously, the application of such methods necessitates their harmonious integration with other factors in the design process and subjecting them to critical aesthetic evaluation.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2023, nr 3 (75), s. 103-113
Keywords: architektura; architecture; geometry; proportion systems; regulating lines; dynamic symmetry; geometria; systemy proporcji; linie regulacyjne; symetria dynamiczna